Management of elevated liver enzymes in geriatric diabetes by yogic practice - K, Beenarani; E, Sreekumaran (International Multidisciplinary Research Journal, 2012)
Objects: The liver plays a major role in the pathogenesis of type 2 diabetes. Moderately elevated liver enzymes are found in type 2 diabetes. This study is designed to appraise the role of yoga on liver enzymes in geriatric type 2 diabetes and consequently, the study constantly monitored the improvement related to glycaemic control during the period of observation. Study design: A total number of 143 type 2 diabetes patients in an age group of 60-70 years with a history of diabetes for 5-10 years and having poor glycaemic control (HbA1c > 8 %) residing in Kozhikode district, Kerala, India participated in this study in test and control group together. The subjects were divided into three groups according to their glycaemic control: group I with HbA1c 8.6 – 9.7 %, group II with HbA1c 9.8 – 10.7 % and group III with HbA1c 10.8 – 12.7 %. The yogic practice sessions for the test group lasted for three months for 90 minutes a day, 6 days a week, under the guidance and supervision of experienced trainers. Each session was systematically divided into structural components with 15 minutes of pranayamas (breath controlling exercises), 10 minutes of warm up exrcises, 50 minutes of asanas (yogic postures) and 15 minutes of supine relaxation in savasana. The control group, mean while, were asked to continue their routine activities like walking and other normal non specific exercises. Glucose, HbA1c, aspartate aminotransferase, alanine aminotransferase and γ- glutamyl transpeptidase were estimated on base line and after 90 days of all the participants. Results: The participants in the test group showed statistically significant (p<0.001) decrease in glucose, HbA1c, and activity of liver enzymes after yogic practice. Conclusions: After 90 days of yogic practices, significant reduction in the liver enzymes was achieved in test group, corresponding to the reduction in blood glucose and HbA1c levels. The findings of this study demonstrate the efficacy of yogic practice, as a therapeutic, preventative and protective agent in geriatric type 2 diabetes mellitus by normalizing the liver function tests along with betterment in their glycaemic condition.